2020
DOI: 10.1097/ijg.0000000000001534
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Success in Selective Laser Trabeculoplasty: Data From the Lausanne Laser Trabeculoplasty Registry

Abstract: Purpose: The purpose of this study was to determine the factors associated with the outcomes of selective laser trabeculoplasty (SLT). Patients and Methods: This was a database analysis (Lausanne Laser Trabeculoplasty Registry) of patients who had SLT between 2015 and 2017. Exclusion criteria were age below 40 years and diagnosis other than ocular hypertension and open-angle glaucoma. Intraocular pressure (IOP) and number of medications were recorded be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…Although no association was found between the higher energy and greater IOP reduction, these authors reported that higher energy was associated with longer duration of qualified success (defined as either >20% reduction in IOP or any reduction in IOP-lowering medications). As both studies by Habib et al28 and Elahi et al,31 were retrospective, IOP reduction may have been influenced by factors other than treatment energy that determine IOP response. No such association was found for complete success (defined as >20% reduction in IOP),31 which is more frequently used as a criterion for a successful SLT treatment 44…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although no association was found between the higher energy and greater IOP reduction, these authors reported that higher energy was associated with longer duration of qualified success (defined as either >20% reduction in IOP or any reduction in IOP-lowering medications). As both studies by Habib et al28 and Elahi et al,31 were retrospective, IOP reduction may have been influenced by factors other than treatment energy that determine IOP response. No such association was found for complete success (defined as >20% reduction in IOP),31 which is more frequently used as a criterion for a successful SLT treatment 44…”
Section: Resultsmentioning
confidence: 99%
“…As both studies by Habib et al28 and Elahi et al,31 were retrospective, IOP reduction may have been influenced by factors other than treatment energy that determine IOP response. No such association was found for complete success (defined as >20% reduction in IOP),31 which is more frequently used as a criterion for a successful SLT treatment 44…”
Section: Resultsmentioning
confidence: 99%
“…When performed over either 180 or 360 degrees, the median reduction in IOP was approximately 20% (range 7%–36%) 42 . This absolute reduction in IOP was greater with a higher pre‐treatment IOP and indeed, a higher pre‐treatment IOP has been the only predictor for greater IOP lowering response 45–48 . Once performed, SLT gradually loses efficacy, with between 45% and 98% of patients maintaining a therapeutic response at 1 year and between 28% and 85% at 3 years 46,49,50 …”
Section: Outcomes Of Sltmentioning
confidence: 99%
“…A study involving 206 patients with ocular hypertension, primary, pseudo-exfoliation, or pigmentary glaucoma has shown IOP reduction following SLT (including both 180° and 360°) to range from 21.8 to 29.0% after six months [ 6 ]. Another study on 170 eyes with ocular hypertension and open-angle glaucoma found a mean IOP reduction of only 17.6% and 18.7% from baseline at years 1 and 2 [ 7 ]. Pre-SLT IOP has been consistently shown to be a predictor of SLT success in terms of IOP reduction [ 7 - 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Other variables, including age, total SLT power, severity of glaucoma (defined clinically), and prior treatments, were not predictive of SLT success or failure [ 10 ]. The other study reports different predictive factors, including male sex, baseline IOP, and medical treatment before SLT [ 7 ]. To address this gap, this study aimed to identify baseline predictors of the IOP-lowering effectiveness of SLT among glaucomatous patients using a mathematical approach.…”
Section: Introductionmentioning
confidence: 99%